Conversational Informatics 2007
DOI: 10.1002/9780470512470.ch9
|View full text |Cite
|
Sign up to set email alerts
|

Facial Gestures: Taxonomy and Application of Nonverbal, Nonemotional Facial Displays for Embodied Conversational Agents

Abstract: Facial displays are an extremely important communication channel fulfilling a wide variety of functions in discourse and conversation. Humans use them naturally, often subconsciously, and are therefore very sensitive to the application of such displays in their computer-generated correspondents, Embodied Conversational Agents (ECA). In this chapter, we aim to provide an extensive survey of one class of facial displays, the facial gestures. Facial gestures include various nods and head movements, blinks, eyebro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The example in the case study in this article focus on the eye signals, eyes are a very important part of the non-verbal signals we send to others. Kinesics ontology contains 15 classes and 319 instances [14]- [16]. Sample of it was illustrated in Fig.…”
Section: Construction Of the Universal Ontology For Scismentioning
confidence: 99%
“…The example in the case study in this article focus on the eye signals, eyes are a very important part of the non-verbal signals we send to others. Kinesics ontology contains 15 classes and 319 instances [14]- [16]. Sample of it was illustrated in Fig.…”
Section: Construction Of the Universal Ontology For Scismentioning
confidence: 99%
“…Verbal communication is a way of conveying one's emotion or meaning via words while non-verbal communication means exchanging information via gestures, facial expressions, or voice rather than words (Knapp & Hall, 2002). Simply put, non-verbal communication is considered an important means of delivering information to others without words (Burgoon, Birk, & Pfau, 1990;Zoric, Smid, & Pandzic, 2007). Birdwhistel (1970) found that words account for just a third of communication, and the remaining two thirds consist of non-verbal channels.…”
Section: Introductionmentioning
confidence: 99%
“…Paralanguage is relevant to the vocal features of language, such as tone, pace of speech, or pitch (Sikorski, 2012); even laughter or no fluencies (e.g., um, ah) are part of paralanguage (Jacobi, 2009). Physical appearance refers to the outward look of a person and includes physical attractiveness, clothing, or hairstyle (Zoric et al, 2007). Proxemics refers to the amount of space and proximity that people feel it necessary to set between themselves and others to have a conversation (Harrigan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While Miller (2005a) states that nonverbal communication includes facial expressions, eye contact, touching, tone of voice, dress, posture, and spatial distance. Perhaps one of the most comprehensive and scientific categorizations of nonverbal communication is offered by Zoric, Smid et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…While it is useful to consider and discuss each category of nonverbal communication individually, it is important to realize that they rarely occur alone. Zoric, Smid et al (2007) describe nonverbal conditions occurring in clusters (multiple displays at one time).…”
Section: Introductionmentioning
confidence: 99%